Hybrid surgery in treatment of pulmonary sequestration with abdominal aorta feeding vessel: a case report - Haining Zhou; Shoujun Tang; Quanshui Fu; Li Yu; Lunxu Liu (Journal of Cardiothoracic Surgery, 2018)
Abstract Background Pulmonary sequestration is a rare congenital pulmonary dysplasia, which requires surgical resection (either via open thoracotomy or video-assisted thoracoscopic surgery [VATS] or via endoluminal occlusion of the abnormal feeding vessel). Case presentation We described a 51-year-old female patient with a history of recurrent cough and repeated pneumonia. She was referred to our hospital for further work-up of pulmonary sequestration. We performed a hybrid surgery (i.e., embolization of the aberrant feeding vessel of the sequestration combined with wedge resection of the left lower lobe lesion through VATS). The patient was discharged on the sixth postoperative day in good condition and without complications. Conclusions We believe that a hybrid operation is safer, more feasible, and more comprehensive than other treatments.